Pengalaman Peran Orang Tua Siswa Kelas 1 dalam Pembelajaran Daring pada Saat Pandemi Covid-19 di Sekolah Madrasah Ibtidaiyah Hidayatul Mubtadiin Desa Kapur - Agus Hardiansyah; Tri Wahyuni; Sri Ariyanti; Lestari Makmuriana (Journal of Education and Culture, 2023)
Since the Covid-19 pandemic, children's education has been carried out remotely. Learning done at home makes the role of parents very important, learning done at home makes the role of parents very important, parents must be able to facilitate learning activities carried out by children, that education should be done as early as possible at home, roles and responsibilities The responsibility lies on the shoulders of parents because parents are the main educators in the family, not only intellectual matters but education for the formation of a noble personality. This role is often referred to as the education of children in the family. The research design used in this study is a qualitative descriptive study, which describes, describes the experience of the role of parents towards children in online learning during the Covid-19 pandemic for grade 1 students of MI (Madrasah Ibtidaiyah) Hidayatul Mubtadiin Kapur Village. The results of this study indicate that the experience of the role of parents of grade 1 students in online learning during the Covid-19 pandemic at the Hidayatul Mubtadiin Madrasah Ibtidaiyah (MI) school in the village of lime. That is, parents carry out two roles at once, first as parents and second as teachers at home; provide facilities and infrastructure for children, and parents as facilitators, motivators, influencers and mentors. And the difficulty of the role of parents of grade 1 students in online learning during the Covid-19 pandemic at the Hidayatul Mubtadiin Madrasah Ibtidaiyah (MI) school, Kapur Village. namely the educational background of parents affects the level of ease and difficulty of parents in educating children, parents who have jobs and the time available.